2018
DOI: 10.1016/j.gie.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic eradication therapy for patients with Barrett’s esophagus–associated dysplasia and intramucosal cancer

Abstract: Barrett's esophagus (BE) is defined by the replacement of the normal squamous epithelium of the distal esophagus with metaplastic intestinal-type columnar epithelium. 1-3 BE is an adverse event of chronic GERD and the only identifiable premalignant condition for esophageal adenocarcinoma (EAC), a cancer that continues to increase in incidence. In 2014 there were approximately 18,170 incident cases of esophageal cancer in the United States, nearly 60% of which were EAC. [4][5][6] Although uncommon, EAC is a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 70 publications
4
88
0
1
Order By: Relevance
“…Endoscopic resection for early esophageal cancer without lymphadenopathy is recommended as alternative to esophagectomy in The National Comprehensive Cancer Network (NCCN) guidelines and the Society of Thoracic Surgeons Guidelines. [6,7] Also NCCN for locally advanced esophageal SCC without distant metastasis recommends for definitive concurrent chemoradiotherapy (CCRT), neoadjucant therapy with surgery or esophagectomy alone. [6] However, health insurance databases or the KCCR are difficult to obtain detailed information regarding cancer stage, clinical characteristics, and treatment modality with outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic resection for early esophageal cancer without lymphadenopathy is recommended as alternative to esophagectomy in The National Comprehensive Cancer Network (NCCN) guidelines and the Society of Thoracic Surgeons Guidelines. [6,7] Also NCCN for locally advanced esophageal SCC without distant metastasis recommends for definitive concurrent chemoradiotherapy (CCRT), neoadjucant therapy with surgery or esophagectomy alone. [6] However, health insurance databases or the KCCR are difficult to obtain detailed information regarding cancer stage, clinical characteristics, and treatment modality with outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic eradication therapy (EET) is a safe and effective treatment for Barrett's esophagus (BE)-related dysplasia and intramucosal esophageal adenocarcinoma (EAC). [1][2][3][4] EET typically involves a combination of therapies including EMR to remove any areas of nodularity or visible focal lesions followed by radiofrequency ablation (RFA) to treat the remaining flat BE with the goal of achieving complete eradication of intestinal metaplasia (CE-IM). However, recurrence of IM, dysplasia, and/or EAC remains a challenge.…”
mentioning
confidence: 99%
“…7 Based on this well-established risk of recurrence after achieving CE-IM, current guidelines recommend that these patients undergo surveillance endoscopies at regular intervals. [1][2][3] During endoscopy, sampling of any visible lesions followed by systematic, 4-quadrant random biopsy sampling every 1 to 2 cm through the length of the original BE segment is suggested. 2,3 These random biopsy specimens serve to identify nonvisible recurrence, which may include microscopic foci of BE or "buried" or subsquamous BE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with BN, endoscopic resection is the preferred therapeutic approach . While both endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) have demonstrated similar efficacy in removal of neoplastic lesions in the esophagus, significant controversy exists over the preferred resection technique and there is a paucity of direct comparisons between the two for the treatment of BN . Several authors have demonstrated no technical advantage of ESD vs. EMR while noting higher rates of complications .…”
Section: Introductionmentioning
confidence: 99%